A review of the mechanism of the central analgesic effect of lidocaine. Issue 17 (April 2020) - Yang, Xi; Wei, Xinchuan; Mu, Yi; Li, Qian; Liu, Jin
Abstract : Abstract: Lidocaine, as the only local anesthetic approved for intravenous administration in the clinic, can relieve neuropathic pain, hyperalgesia, and complex regional pain syndrome. Intravenous injection of lidocaine during surgery is considered as an effective strategy to control postoperative pain, but the mechanism of its analgesic effect has not been fully elucidated. This paper intends to review recent studies on the mechanism of the analgesic effect of lidocaine. To the end, we conducted an electronic search of the PubMed database. The search period was from 5 years before June 2019. Lidocaine was used as the search term. A total of 659 documents were obtained, we included 17 articles. These articles combined with the 34 articles found by hand searching made up the 51 articles that were ultimately included. We reviewed the analgesic mechanism of lidocaine in the central nervous system.